117k views
2 votes
3 x + 2 y = 6
4 x + y = 1 Solve the system of equations.

User Edoput
by
5.2k points

1 Answer

3 votes

3x + 2y = 6

4x + y = 1

Solve the second equation for y:

y = -4x + 1

Substitute -4x + 1 for y in the first equation.

3x + 2(-4x + 1) = 6

3x - 8x + 2 = 6

-5x = 4

x = -4/5

Now substitute x with -4/5 in the first original equation.

3x + 2y = 6

3 * (-4/5) + 2y = 6

-12/5 + 2y = 6

-12 + 10y = 30

10y = 42

y = 42/10

y = 21/5

Solution: (-4/5, 21/5)

Hope this helped! ~

User Inkeliz
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.